Food security and the EU's common agricultural policy: Facts against fears - Valentin Zahrnt (European Centre for International Political Economy (ECIPE), 2011)
Fears about food security in the EU have become a driving force in the debate about the future Common Agricultural Policy (CAP). But the facts do not bear out these fears. This paper brings together the available evidence against EU food security concerns: the size of EU production, the even greater EU production potential and the reliability of imports. It also looks at the argument that a strong CAP is needed to feed the world. While hunger in developing countries is undeniably a most serious problem, paying direct income support to European farmers is a most inefficient response. It would be preferable to invest the money to boost agricultural productivity in developing countries.
Keywords: Q17; Q18; 330; Food security; Food prices; Common Agricultural Policy; Agriculture in International Trade; EU-Agrarpolitik; Kritik; Lebensmittelpreis; Ernährungssicherung; Agraraußenhandel; EU-Staaten